Utilization Of Loose Parts Media In Developing Early Childhood Creativity - Isjayanti, Nur; Hastuti, Isnaiani Budi (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to determine the effectiveness of learning using loose parts media to stimulate the creativity of early childhood students in BA Aisyiyah Kriwen 2, Sukoharjo District, Sukoharjo Regency. Methodology: The research uses a qualitative approach with data collected through observation, interviews, and documentation. The data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. Results: The findings reveal that after implementing loose parts media in learning, children became more creative, showed courage in creating works, and developed greater independence. Additionally, the children appeared happy and engaged, as the activities allowed them to play while learning. Applications/Originality/Value: This study highlights the importance of using varied and stimulating media—such as loose parts—in early childhood education to promote creativity, independence, and enjoyment in learning. It demonstrates how creative materials can effectively support holistic development when integrated into teaching strategies.